Analisis Motivasi Kerja Guna Meningkatkan Produktivitas Kerja Pada Karyawan UMKM Cookies & Dessert By Me Cikarang - Amelia, Yuni Putri; S, Sungkono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study is to examine the connection between worker productivity and job motivation at UMKM Cookies and Dessert By Me in Cikarang. Descriptive qualitative research methodology is used to examine the issue of work motivation and how it affects productivity in the setting of MSMEs. Employees are the most valuable source of labor production in the corporate sector, according to research. They contribute significantly to it. A company's ability to succeed or fail is determined by how persistent and productive its personnel are. Human resource development interventions are essential for enhancing the efficacy and competency of the workforce, emphasizing the significance of fostering a positive and encouraging work environment to boost output. The findings show that factors such as active involvement of the owner in task setting, pleasant work environment, constructive feedback, clear target setting, and job matching with skills, significantly contribute to increasing employee productivity. This approach not only supports the achievement of MSME business goals but also maintains employee satisfaction and engagement. Cookies and Dessert By Me's implementation of effective work motivation strategies has shown promising results, proven by increased daily sales thanks to collaborative efforts between owners and employees during production. Effective work motivation practices, facilitated by the owner's involvement in daily activities and direct guidance, have contributed to improved work results and business success. Thus, effective management of work motivation in MSMEs such as Cookies and Dessert By Me can be considered a key strategy in strengthening the productivity and success of the organization as a whole.